ASPEK REPRODUKSI UDANG MANTIS Harpiosquilla raphidea DI EKOSISTEM MANGROVE KABUPATEN LABUHANBATU, SUMATERA UTARA - Selly Artika Dewi Hasibuan; Rivo Hasper Dimenta (Jurnal Biolokus: Jurnal Penelitian Pendidikan Biologi dan Biologi, 2022)
This study aims to inform about the gonadal maturity level, gonadal maturity index, the first body size of maturity (L50), and the fecundity of Harpiosquilla raphidea in Labuhanbatu regency waters, North Sumatera. The study was conducted for three months from December 2021 to February 2022 with samplings were conducted twice a month. The purposive random sampling method used to determine of three stations of this research. Samples of H. raphidea were caught with shrimp trawl nets.  The results describe that population of mantis shrimp H. raphidea in Labuhanbatu regency were dominate in first gonad maturity stage. The Gonad Somatic Index (GSI) value of male H. raphidea mantis ranged from 6.00 – 11.87 and the female ranged from 5.12 – 12.75. The first maturity size of male were 19.88 cmBL and female H. raphidea were 18.75 cmBL. The fecundity of this mantis shrimp H. raphidea  in station research ranged from 130,088 to 970,658.